Examination of Failures in the Marine Fuel and Lube Oil Separators Through the Fuzzy DEMATEL Method - Ayvaz, Sercan; Karakurt, Asim Sinan (GALENOS PUBL HOUSE, 2025)
Separators are essential equipment on ships, regardless of the vessel type or the type of engine installed, whether the main, and auxiliary engines are two-stroke or four-stroke. The primary function of these separators, apart from the bilge separator, is to ensure clean fuel delivery to the main engine and auxiliary machinery by removing water and solid contaminants from the fuel. The efficiency of the separators and the level of maintenance they receive directly influence the performance of the ship's machinery, reducing the likelihood of malfunctions and power loss in systems dependent on clean fuel. However, since separators operate at high speeds using centrifugal force and are composed of numerous intricate components, they are prone to potential failures if not properly maintained. While preparing for this study, four experts were asked about the effects of failures that may occur in the separators. According to the criteria received, the fuzzy DEMATEL method, a multi-criteria decision-making method, was used to evaluate the effects of failures. When the results are examined, the most effective factors are the wear of the bearings, contamination, incorrect assembly of the bowls, and bending of the shaft. It is extremely important to have spare parts available on the ship and to maintain the equipment with sufficient authorized crew.
Keywords: Failure; Fuzzy; DEMATEL; Multi-criteria decision making; Separator; HUMAN RELIABILITY-ANALYSIS; DECISION-MAKING; EXTENSION; SELECTION; REPAIR; SHIPS; Engineering; Transportation